2019
DOI: 10.1080/13814788.2019.1668372
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study examining everyday frailty management strategies adopted by Polish stakeholders

Abstract: Background: Frailty is a multidimensional clinical state that is common in older age and can be managed through intervention. Strategies to manage frailty have not been previously explored with stakeholders in Poland. This may stem from misperceptions about the nature and malleability of frailty, which has resulted in it being viewed as a lower priority healthcare concern.Objectives: To explore stakeholders’ views to determine whether there are effective everyday strategies that they can adopt to reduce, rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 31 publications
1
11
0
2
Order By: Relevance
“…The perceptions of frailty among HCPs are consistent with literature findings describing a dynamic, multi-dimensional geriatric condition, often triggered by illness or an acute event and which has the potential to be improved [19][20][21] . However, dissent was evident in views regarding specific markers for frailty and its' reversibility.…”
Section: Discussionsupporting
confidence: 84%
“…The perceptions of frailty among HCPs are consistent with literature findings describing a dynamic, multi-dimensional geriatric condition, often triggered by illness or an acute event and which has the potential to be improved [19][20][21] . However, dissent was evident in views regarding specific markers for frailty and its' reversibility.…”
Section: Discussionsupporting
confidence: 84%
“…Regarding the measurement of frailty, five articles used the Clinical Frailty Scale 11,15,[22][23][24] , four used the Frailty Phenotype 14,23,25,26 , three used the Tilburg Frailty Indicator [27][28][29] , two used the Comprehensive Frailty Assessment Instrument 10.30 , five defined frailty without an instrument or objective measurement 4.14. [31][32][33] , one article used Prisma-7 6 and one the Edmonton Frailty Scale 34 . Of these, in two articles 14,23 there was the combination of more than one instrument.…”
Section: Resultsmentioning
confidence: 99%
“…This category addresses how older adults perceive frailty. The older adults' view of frailty is recurrent as a negative, harmful, rejected and associated label, with worsening health conditions, reduced participation and increased stigmatization 11,15,25,32 . A qualitative study on the perception and attitude of older adults towards frailty identified a discrepancy between operationalization in clinical contexts and the understanding of older adults 11 .…”
Section: Frailty From the Perception Of The Frail Older Personmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychological and socioeconomic factors were perceived to have a major impact on frailty by PHC professionals in our study. Similarly, in another study examining everyday frailty management strategies by Polish stakeholders, professionals stated that frailty was often initiated by a lack of mental wellbeing, due to psychological hardships, social isolation and loneliness, and they suggested that frailty is caused by the psychological inability to cope with illness [ 23 ]. In a Swedish study exploring healthcare professionals’ views, frailty was perceived as a multidimensional concept with several interacting aspects.…”
Section: Discussionmentioning
confidence: 99%